Grafos em superfícies - Takahama, Mariana Thieme Moraes [UNESP] (2014)
The main goal of this work is to get a result on separation of surfaces by graphs. The Relative Homology is the principal tool used and we get a particular version of Lefschetz duality. For the preparation of this dissertation we studied: graphs, simplicial homology, relative homology and graphs on surfaces. The study was based on the book Graphs, Surfaces and Homology of P. J. Giblin